Patient's Perspectives of Experimental HCV-Positive to HCV-Negative Renal Transplantation: Report from a Single Site. Issue 1 (2nd January 2020) - Van Pilsum Rasmussen, Sarah E.; Seaman, Shanti; Brown, Diane; Desai, Niraj; Sulkowski, Mark; Segev, Dorry L.; Durand, Christine M.; Sugarman, Jeremy
Abstract: Background: With growing transplant wait times, clinical trials are evaluating the safety and efficacy of transplanting HCV-infected donor (HCV+) organs into HCV-noninfected recipients (HCV D+/R-). Such transplants raise ethical questions about safety, consent, and access to organs. Methods: We interviewed eight of the ten total HCV D+/R- transplant recipients enrolled in a pilot clinical trial examining the safety and feasibility of these novel transplants regarding their experiences in the trial, including their decision-making and perceptions of the informed consent process. Results : All interviewees reported positive experiences and expressed confidence regarding their decision to participate. Participants accepted an HCV + organ based on their assessments of the risks and potential benefits of HCV D+/R- transplants. For many, the risks of HCV were minimal compared to the risks of not receiving a transplant. All participants recalled providing informed consent, reporting that the process was thorough and that all their questions were addressed. Participants did not regret receiving an HCV D+/R- transplant and did not report experiencing stigma. However, given their understanding of HCV cure rates in the general population and the survival benefit associated with kidney transplantation, participants may have conflated research regarding HCV D+/R- transplantation with clinical care, suggesting a potential therapeutic misconception. Conclusions: Recipients of experimental HCV D+/R- transplants generally seemed to recognize the risks and benefits of these novel transplants and did not regret participating. Such salutary reported experiences are important in assessing the appropriateness of further research into the feasibility of HCV D+/R- transplants.